Socio-Economic Losses of Small Fishermen after Lobster Seeding Banning Policy (Case Study in Batu Nampar Selatan Village, East Lombok Regency) - Syarif Husni; M. Yusuf; Muhammad Nursan; Aeko Fria Utama FR (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ The objectives of this study are: 1) to find out the perceptions of small fishermen about PERMEN KP No.1 / 2015 in conjunction with Minister of Marine Affairs and Fisheries Regulation No.56 / 2016, 2) to calculate the social losses of small fishermen after the prohibition policy on the prohibition of fishing for lobster seeds, 3) to calculate the economic losses of small fishermen after lobster seed fishing prohibition policy. This research uses descriptive methods and case studies. Apart from interviews with respondents, it was also conducted using the Focus Group Discussion (FGD) method. The number of respondents was determined as many as 30 people by simple random sampling and the data analysis used consisted of descriptive analysis based on tabulations, and after processing it was presented in tabular form, analysis of people's work days (HKO) and analysis of costs and income.ÃÂ The results showed: 1) The most dominant perception of fishermen is that the existence of the Minister of Marine Affairs and Fisheries Regulation needs to be reviewed and the compensation provided by the government is not in accordance with the conditions of fishermen 2) Social losses for fishermen in terms of employment of 208 HKO / year, and 3) Economic losses, namely the loss of income of small fishermen of 121,329,000 IDR/ year.